Métodos de conservação do restolho de abacaxi ‘pérola’ para alimentação de ruminantes - SILVA, Raphael Ramos (2018)
The objective of this study was to determine the nutritive value of 'Pérola' pineapple (RA) stover in two ways of preservation, in the form of silage with different levels of leucine hay and ammonia. The research was conducted in the forage sector of the Federal University of Maranhão, in Chapadinha, MA. For the two experiments, a completely randomized design was used, six treatments (PS pre-wilting and 0, 10, 20, 30 and 40% inclusion of leucine hay based on natural matter) were tested for silage, with five replicates and for the ammonization, five treatments (0, 2, 4, 6 and 8% of urea based on dry matter), with four replicates. The content of dry matter, crude protein, lignin and pH of the silage increased linearly (P <0.05) as a function of the inclusion of leucine hay, while buffer power, soluble carbohydrate content and effluent losses presented linear behavior negative. For the variables gas loss and dry matter recovery, quadratic behavior (P <0.05) was observed according to the addition of leucene hay. There was no effect of treatments on NDF, FDA, hemicellulose and ash data. Regarding the ruminal disappearance of DM, there was an effect of leucine addition (P <0.05) and incubation times (P <0.05). With the increase of inclusion levels, there was a decrease in the ruminal disappearance of DM. The disappearance of DM from the PS pre-wilting showed differences of the treatments with 30 and 40% of hay inclusion in the incubation time 72h. The values of fraction a were similar to each other, except that observed for PSPW. Potentially degradable insoluble fraction and potential degradation increased when 10% leucine hay was added and then decreased with increasing inclusion levels. The effective DM degradability presented the highest values for the silages with or without the lowest inclusion levels of leucine hay. Regarding the ammonization results, the dry matter presented a linear behavior LRP (Linear Response Plateau), showing a reduction and then remained constant. PB presented a linear increasing effect (P <0.05) as urea levels increased, ranging from 5.74% to 19.41% for urea levels and 8%, respectively. For NDF and hemicellulose, there was a linear decrease (P <0.05) of 0.5% and 0.53%, respectively, for each 1% of added urea. There was no effect of urea levels on acid and lignin detergent fiber contents, which presented mean values of 30.75% and 5.10%, respectively. There was an effect (P <0.05) of the incubation time on the disappearance of MS and NDF, but the same was not observed (P> 0.05) between urea levels and for urea interaction x incubation time. Treatment of RA hay with urea did not influence the soluble fraction of DM, however, treatment with 4% of urea gave an increase of 6.94% and 6.04% for fraction b and for the potential degradability of DM, respectively. The ammonia process did not affect the effective DM degradabilities, which presented a mean of 56.4%, 45.8% and 40.9% for the rates 2% / h, 5% / h and 8% / h, respectively. The urea levels had a reduced effect on the degradability parameters of the NDF, with a reduction of only 2.9 percentage points in the non degradable standardized fraction, comparing the control with the inclusion of 8% of urea, reflecting a reduced alteration in the potentially degradable fraction and in the passing rate. Pineapple stover both in the form of silage associated with 10% inclusion of leucine hay and in ammonized hay conditions presents satisfactory nutritional value for ruminant feed.